Respiratory medication used in COPD patients from seven Latin American countries : The lassyc study (2018)
Background: Limited information is available regarding medication use in COPD patients from Latin America. This study evaluated the type of medication used and the adherence to different inhaled treatments in stable COPD patients from the Latin American region. Methods: This was an observational, cross-sectional, multinational, and multicenter study in COPD patients attended by specialist doctors from seven Latin American countries. Adherence to inhaled therapy was assessed using the Test of Adherence to Inhalers (TAI) questionnaire. The type of medication was assessed as: short-acting β-agonist (SABA) or short-acting muscarinic antagonist (SAMA) only, long-acting muscarinic antagonist (LAMA), long-acting β-agonist (LABA), LABA/LAMA, inhaled corticosteroid (ICS), ICS/LABA, ICS/LAMA/LABA, or other. Results: In total, 795 patients were included (59.6% male), with a mean age of 69.5±8.7 years and post-bronchodilator FEV1of 50.0%±18.6%. The ICS/LAMA/LABA (32.9%) and ICS/LABA (27.7%) combinations were the most common medications used, followed by LABA/LAMA (11.3%), SABA or SAMA (7.9%), LABA (6.4%), LAMA (5.8%), and ICS (4.3%). The types of medication most commonly used in each Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2013 category were ICS/LABA (A: 32.7%; B: 19.8%; C: 25.7%; D: 28.2%) and ICS/LAMA/LABA (A: 17.3%; B: 30.2%; C: 33%; D: 41.1%). The use of long-acting bronchodilators showed the highest adherence (good or high adherence >50%) according to the TAI questionnaire. Conclusion: COPD management in specialist practice in Latin America does not follow the current guideline recommendations and there is an overuse of ICSs in patients with COPD from this region. Treatment regimens including the use of long-acting bronchodilators are associated with the highest adherence. © 2018 Casas et al.